Atividade reprodutiva de Scinax rizibilis (Bokermann) (Anura, Hylidae) na Floresta Atlântica, sudeste do Brasil - Bastos, Rogério P; Haddad, Celio Fernando Baptista [UNESP] (Sociedade Brasileira de Zoologia, 1999)
The breeding activity of Scinax rizibilis (Bokermann, 1964) was observed in a temporary pond, in the municipality of Ribeirão Branco, in the Southern São Paulo State from February 1993 to January 1994 and November 1994 to February 1995. The reproductive season extended from September to February. Females were larger and heavier (after oviposition) than males. In the choras, the spatial distribution tended towards uniformity. The number of males and females in the chorus was positively correlated. However there was no correlation between the number of males and the estimation of the operational sex ratios. on average there were seven males for each female present in the chorus. The males were apparently selected by females.
Breeding activity of the treefrog Scinax rizibilis (Bokermann) (Anura, Hylidae) in the Atlantic Forest, Southeastern, Brazil
Keywords: Hylidae; Scinax rizibilis; reproduction; sexual selection; spatial distribution; seasonality